Pelatihan Pemanfaatan Media SenCleTi (Sensory Circle Time) dalam Pengoptimalan Keterampilan Guru untuk Mendukung Kurikulum PAUD - Sherly Utami, Winda; Indriani Harianja, Sri; Siregar, Masyunita; Muazzomi , Nyimas; Indryani, Indryani (Pendidikan Sejarah FKIP Universitas JAMBI, 2025)
Providing quality education expects teachers to be creative and innovative individuals, so that all aspects of development, especially sensory-motor development, can develop according to the child's age stage. An alternative that can improve sensory-motor development is through the use of active and interactive learning media. Sencleti (sensory circle time) is one active and interactive learning media that improves sensory-motor aspects. Simply put, Sencleti provides a varied learning process by engaging all five senses in a single game theme. Sencleti (sensory circle time) is a game media consisting of many themes. This learning media is very easy for teachers to create, because the materials used are not difficult to find. The purpose of this community service activity is to provide mentoring to PAUD teachers to improve their skills and knowledge in utilizing learning media to create interesting and engaging activities, especially for improving the sensory-motor skills of early childhood. The stages in this community service include activity planning, design preparation, activity implementation, and activity evaluation. The results of the community service activity show an increase in the skills and knowledge of teachers regarding sencleti (sensory circle time) learning media for early childhood sensory-motor skills. Thus, it can be concluded that this mentoring activity provides a positive contribution for teachers in increasing their insight into sencleti (sensory circle time) learning media that can support learning activities in PAUD institutions.